Styrene–Maleic Acid Copolymer-Based Nanoprobes for Enhanced Boron Neutron Capture Therapy - Mingjie Zhang; Shanghui Gao; Kai Yang; Benchun Jiang; Wei Xu; Waliul Islam; Shinnosuke Koike; Yusei Kinoshita; Hiroto Nakayama; Jianrong Zhou; Kazumi Yokomizo; Jun Fang (Pharmaceutics, 2025)
Background/Objectives: Boron neutron capture therapy (BNCT) is a promising, less-invasive anticancer treatment. However, the development of effective boron-based agents (BNCT probes) remains a critical and challenging issue. Previously, we developed a styrene–maleic acid (SMA) copolymer conjugated with glucosamine, encapsulating boronic acid, which exhibited tumor-targeted distribution via the enhanced permeability and retention (EPR) effect. Building upon this approach, in this study, we designed and synthesized a series of SMA-based polymeric probes for BNCT and evaluated their biological activities, with a particular focus on tumor-targeting properties. Methods: Two SMA-based BNCT nanoprobes, SMA–glucosamine conjugated Borax (SG@B) and SMA-conjugated aminophenylboronic acid encapsulating tavaborole (S-APB@TB), were designed and synthesized. The boron content in the conjugates was quantified using inductively coupled plasma mass spectrometry (ICP-MS), while particle sizes were measured via dynamic light scattering (DLS). In vitro cytotoxicity was assessed using the MTT assay in mouse colon cancer C26 cells. The tissue distribution of the conjugates was analyzed in a mouse sarcoma S180 solid tumor model using ICP-MS. Results: Both SG@B and S-APB@TB formed nanoformulations with average particle sizes of 137 nm and 99 nm, respectively. The boron content of SG@B was 2%, whereas S-APB@TB exhibited a significantly higher boron content of 14.4%. Both conjugates demonstrated dose-dependent cytotoxicity against C26 cells, even in the absence of neutron irradiation. Notably, tissue distribution analysis following intravenous injection revealed higher boron concentrations in plasma and tumor tissues compared to most normal tissues, with S-APB@TB showing particularly favorable tumor accumulation. Conclusions: These findings highlight the tumor-targeting potential of SMA-based BNCT nanoprobes. Further investigations are warranted to advance their clinical development as BNCT agents.